Research of the Inverse of Tooth Surface Friction Coefficient based on Intergeneration Projection Genetic Algorithm - Fu Shuangxue; Liu Dayong (Jixie chuandong)
The precise gear model is built by the method for composite modeling with MATLAB and APDL. The key friction characteristic parameter is acquired by test. The tooth surface friction coefficients are inversely analyzed by numerical simulation and intergeneration projection genetic algorithms（ IP- GA） under different lubrication conditions. The problem of complex tooth surface friction coefficients is solved reasonably.Compared with traditional method,the actual tooth friction conditions are simulated,then the result is more reasonable. Exactly inverse analysis of tooth friction coefficients can help to numerical simulation and improve dynamic performance of gear transmission and to upgrade the level of design and manufacture of gear.